Effects of Al:Si and (Al + Na):Si ratios on the properties of the international simple glass, part II: Structure. Issue 1 (27th September 2020) - Lu, Xiaonan; Reiser, Joelle T.; Parruzot, Benjamin; Deng, Lu; Gussev, Igor M.; Neuefeind, Jörg C.; Graham, Trent R.; Liu, Hongshen; Ryan, Joseph V.; Kim, Seong H.; Washton, Nancy; Lang, Maik; et al.
Abstract: High‐alumina containing high‐level waste (HLW) will be vitrified at the Waste Treatment Plant at the Hanford Site. The resulting glasses, high in alumina, will have distinct composition‐structure‐property (C‐S‐P) relationships compared to previously studied HLW glasses. These C‐S‐P relationships determine the processability and product durability of glasses and therefore must be understood. The main purpose of this study is to understand the detailed structural changes caused by Al:Si and (Al + Na):Si substitutions in a simplified nuclear waste model glass (ISG, international simple glass) by combining experimental structural characterizations and molecular dynamics (MD) simulations. The structures of these two series of glasses were characterized by neutron total scattering and 27 Al, 23 Na, 29 Si, and 11 B solid‐state nuclear magnetic resonance (NMR) spectroscopy. Additionally, MD simulations were used to generate atomistic structural models of the borosilicate glasses and simulation results were validated by the experimental structural data. Short‐range (eg, bond distance, coordination number, etc) and medium‐range (eg, oxygen speciation, network connectivity, polyhedral linkages) structural features of the borosilicate glasses were systematically investigated as a function of the degree of substitution. The results show that bond distance and coordination number of the cation‐oxygen pairs are relatively insensitive to Al:Si and (Al + Na):Si substitutions with the exception of the B‐O pair. Additionally, the Al:Si substitution results in an increase in tri‐bridging oxygen species, whereas (Al + Na):Si substitution creates nonbridging oxygen species. Charge compensator preferences were found for Si‐[NBO] (Na + ), [3] B‐[NBO] (Na + ), [4] B (mostly Ca 2+ ), [4] Al (nearly equally split Na + and Ca 2+ ), and [6] Zr (mostly Ca 2+ ). The network former‐BO‐network former linkages preferences were also tabulated; Si‐O‐Al and Al‐O‐Al were preferred at the expense of lower Si‐O‐ [3] B and [3] B‐O‐ [3] B linkages. These results provide insights on the structural origins of property changes such as glass‐transition temperature caused by the substitutions, providing a basis for future improvements of theoretical and computer simulation models.